Application of the project based learning model based on lesson study to improve Students' critical thinking skills - Rani Tania Pratiwi; Caecilia Dina Rosaline; Atin Nuryatin; Dewi Ningrum Agustin; Deden Agustira; Yulianti Yulianti; Tati Rahmawati; Muhammad Fahmi Fadli Rifa'i (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This research aims to enhance critical thinking skills using the Lesson research-based project-based learning (PjBL) model in improving the critical thinking skills of grade VII students in social studies subjects at SMP Negeri 4 Ciawigebang. The theory supports this research. According to Trianto, which states that "the purpose of this PjBL method has the following objectives: 1) to provide broad insight into students when facing problems directly; 2) developing critical thinking skills and expertise in dealing with problems that are received directly". The problem addressed in this research is the low critical thinking ability of students, characterized by their dependence on reading books and a lack of initiative in solving problems independently. The research method employed was a quasi-experimental design with a non-equivalent control group. This research involved two groups of students: the experimental group, which received project-based learning (PjBL) based on Lesson research, and the control group, which used the lecture method. The analysis results showed a significant difference in critical thinking skills between the experimental and control groups. Thus, the research-based Lesson Project-based Learning (PjBL) learning model can be an effective alternative for developing students' critical thinking skills in secondary school.